Evaluation of the use of a Laser Tracker and an Indexed Metrology Platform as Gauge Equipment in Articulated Arm Coordinate Measuring Machine Verification Procedures. (2015) - Acero, R.; Brau, A.; Santolaria, J.; Pueo, M.; Cajal, C.
Abstract: The development of new gauges and alternative calibration and verification techniques applied to articulated arm coordinate measuring machine (AACMM) has been approached in different ways. In this work the analysis of the use of a laser tracker (LT) as reference instrument in calibration and verification procedures for AACMM together with an indexed metrology platform (IMP) replacing the conventional one-dimensional gauges is presented. This technique avoids the need of materializing the length required in a conventional gauge, increasing the flexibility for defining test positions and broadening the definition of reference lengths depending on equipment calibration or verification requirements. The use of the IMP in this verification procedure enables a reduction of testing time and space needed in the data capturing process. The results obtained showed the suitability of the proposed procedure using the LT as reference instrument.